Chitosan‐Supported Copper(II) Schiff Base Complexes: Applications in Synthesis of 5‐Substituted 1H‐Tetrazoles and Oxidative Homo‐Coupling of Terminal Alkynes. Issue 23 (16th August 2017) - Anuradha; Layek, Samaresh; Agrahari, Bhumika; Pathak, Devendra Deo
Abstract: Two new Chitosan‐supported Schiff base complexes (CS@L1 ‐Cu) and (CS@L2 ‐Cu) have been synthesized. They are characterized by various spectroscopic and instrumental techniques such as Fourier transform infrared spectroscopy (FT‐IR), Ultravoilet‐visible spectroscopy (UV‐Vis), X‐ray diffraction (XRD), X‐ray photoelectron spectroscopy (XPS), Field emission scanning electron microscopy (FESEM), Energy dispersiveX‐ray microscopy (EDX), Thermo gravimetric analysis/Differential thermal analysis (TGA/DTA), and atomic absorption spectroscopy (AAS) analysis.Thecomplex CS@L2 ‐Cu have been found to be efficient heterogeneous catalyst for the synthesis of 5‐substituted 1 H ‐tetrazoles from a series of oximes and sodium azide and also for oxidative homo‐coupling of terminal alkynes. The catalyst could be easily recovered from reaction mixture by simple filtration and recycled up to five times with no significant loss in its catalytic activity. The mercury poisoning test indicated that the catalysts are heterogeneous in nature. All products were isolated as white to off‐white and light yellow solids and characterized by 1 H and 13 C NMR spectroscopy. Abstract : Chitosan‐supported Schiff base Copper(II) complexes (CS@L1 ‐Cu and CS@L2 ‐Cu) were synthesized and thoroughly characterized by various spectroscopic and instrumental techniques. The complex CS@L2 ‐Cu exhibited high catalytic activity for the synthesis of 5‐substituted 1 H ‐tetrazoles with good to excellent yield (78 %‐97 %). The complex CS@L2 ‐Cu also shows high catalytic activity for the oxidative homo‐coupling of alkynes with moderate to good yield (63 %‐91 %). The catalyst can be reused up to five times with no significant loss of catalytic activity.